Financial Crises (IntechOpen, 2024)
Financial Crises - Challenges and Solutions examines why and how financial crises occur and what can be learned from past crises. It puts forth possible solutions to avoid the recurrence of crises and offers empirical evidence and policy implications, making it a useful resource for researchers in finance.